Elastoplastic and fracture behaviour of semi-crystalline polymers under multiaxial stress states - Joo P. Manaia; Francisco A. Pires; Ablio M. P. de Jesus (Fracture and Structural Integrity)
The deformation behaviour and fracture mechanisms of highdensity polyethylene (HDPE), polypropylene (PP) and polyamide 6 (PA 6) are investigated experimentally under different stress states and at different crosshead speeds of 1, 20 and 200 mm/min. Fracture surface morphologies were investigated in a series of specimens tested at 200 mm/min under combined tension/shear loading at three different loading angles ( ? = 0, 30deg and 90deg) at room temperature (RT) and 50 C. In addition, the effects of notch profile radii (stress triaxiality) on HDPE, PP and PA 6 fracture behaviour have been studied at RT, using flat and cylindrical notched specimens. Specimens geometries were carefully designed to achieve various loading conditions and allowing to explore initial stress triaxialities ranged from 0 in pure shear loading ( ? = 0) to a maximum of 0.84 for flat notched specimens with radius of 5 mm. The yield load shows an explicit dependency on temperature and crosshead speed. The fracture surfaces analysed reveals damage mechanisms such as crazing, void and cavitation formation. Two or more mechanisms are predominant, which means that the stresses along fracture process are not uniform.